Penerapan Metode Smart pada Sistem Pendukung Keputusan Pemilihan Ustadz Terbaik Rumah Tahfidz Al-Firdaus - Rachmad, Muhammad Ichsan Farel; Sanjaya, M. Rudi; Wijaya Putra, Bayu; Indah, Dwi Rosa (Institut Teknologi Garut, 2025)
This study aims to develop a decision support system for selecting the best ustadz by applying the SMART (Simple Multi Attribute Rating Technique) method at Rumah Tahfidz Al-Firdaus Banyuasin. The institution faces challenges due to the absence of a formal procedure for objectively and measurably identifying outstanding instructors. The SMART method is employed because it enables transparent decision-making through systematic calculations based on predefined weights and parameters. The research adopts the Waterfall development model, which includes requirement analysis, design, implementation, testing, and maintenance phases. The evaluation parameters include attendance level, frequency of lateness, professional behavior, teaching techniques, team collaboration, and guidance in memorizing the Qur’an. This study contributes to the development of decision support systems in tahfidz institutions by adapting the SMART method to assessment criteria specific to Qur’anic learning. The findings show that the application developed is capable of assisting management in objectively measuring and determining the best ustadz, while also simplifying the performance evaluation process. Black-box testing confirms that all system features operate in accordance with the initial design, and the SMART calculation output successfully generates an automatic ranking of the top instructors. The presence of this system makes the assessment process more efficient, accurate, and sustainable, thereby supporting the improvement of teaching quality in Qur’an-based educational institutions.